From Brieger’s Winery to Greek Orthodox Church - Wanatko, Grzegorz (In Gremium. Studies in History, Culture and Politics, 2019)
Zielona Góra has a flourish tradition in production of wine. City itself reminds us about it in many objects. One of them is building of a former winery of Fritz Brieger. This marchant and wine producer build it in 1880. After his dead in 1918, his niece Martha Gischke was looking after the winery. In the interwar period its status was changed, but the profil of production remained the same, such as the name of company. During World War II the last rebuild of the object has been made. After WW II building was taken by polish administration. In 1945 production of wine returned. In the object started its activity the company of Stanisław Marczyński, and after a couple of months his factory was functioned as a Antoni Kulesza Wine Factory. In 1951 an object has been taken by Lubuskie Wine Factory. Some of the rooms were taken as a normal apartments but bulding was in hands of a company to 1999. From the beginnings of XXI Century we can observe a new destination of this place. In 2003 object was sold to Greek Orthodox Church in Zielona Góra. Adaptation of the building to sacral activities tooked couple of years. The building has been consecrated in 2008. Since then it is The Greek Othodox Church of St Mary.